Government Policy Towards the Marine Fence Polemic in Tangerang (Civil Law Review of Coastal Areas Control Rights) - Suwarni, Ayni; Dewi, Aliya Sandra (Journal of Governance, 2025)
The construction of a marine fence in Tangerang limits access for coastal communities, especially fishermen, to marine resources. This is an unlawful act (PMH) based on Article 1365 of the Civil Code. The construction of a sea fence also creates a conflict between the interests of the developer and the interests of the community. This research aims to analyze government policy in dealing with the maritime fence polemic in Tangerang. This research uses normative juridical methods with statutory, conceptual, and case approaches. The data analysis technique used is qualitative analysis with a descriptive-analytical approach. Research findings show that the construction of the sea wall in Tangerang was carried out without proper permits and violated Law Number 27 of 2007 concerning Management of Coastal Areas and Small Islands. In addition, this action has the potential to harm the community both economically and socially, giving them the legal right to file civil claims for compensation or dismantling of the seawall. Regarding dispute resolution mechanisms, this study found that mediation and negotiation are more effective options than litigation. concluded that the construction of a sea wall in Tangerang violates civil law principles. The legal implications include potential civil claims based on Article 1365 of the Civil Code, as well as claims for compensation from affected communities. The recommendation of this research is that the government must strengthen regulations and licensing mechanisms and transparency of coastal infrastructure projects to prevent illegal land occupation in the future.